Familial Mediterranean Fever Complicated by Avasculer Necrosis of the Femoral Head, Spondiloarthropathy and Osteoporosis: Case Report - Cengiz Bahadır,; Feride Ocak,; Burcu Önal,; Bünyamin Öztürk,; Özbil Korkmaz,; Can Bora Önder, (Archives of Rheumatology, 2007)
Familial Mediterrenean Fever (FMF) is a hereditary disease characterized by recurrent atacks of fever and serositis. In the clinical course of the disease also locomotor system symptoms frequently occur. In these patients seronegative spondiloartropathy, osteoporosis, arthritis and rarely avasculer necrosis of the femoral head may be seen. Although the relationship of FMF and spondyloarthropathy is a well established situation, there is not enough information about concomitance of FMF and avascular necrosis. In this report a case which has all locomotor system complications of FMF including avascular necrosis is discussed in the light of relevant literature. (Rheumatism 2007; 22: 36-9)